2014
DOI: 10.1111/tct.12100
|View full text |Cite
|
Sign up to set email alerts
|

A prescribing e-tutorial for medical students

Abstract: Our e-tutorial is effective and meets the needs of medical students. Once the e-tutorial is disseminated more widely and is expanded by user-contributed questions, we hope that it will become established as a national platform for collaborative prescribing education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…DISCUSSION Previous studies have described benefits associated with the blended approach of studying to a variety of subject matters, including human anatomy (Catling et al, 2014;Durham, Brettell, Summerside, & McHanwell, 2009;Pereira et al, 2007). In fact, participants in one of the research project definitively outperformed those in the traditional curriculum (Pereira et al, 2007).…”
Section: ) Quantitative Commentsmentioning
confidence: 85%
See 1 more Smart Citation
“…DISCUSSION Previous studies have described benefits associated with the blended approach of studying to a variety of subject matters, including human anatomy (Catling et al, 2014;Durham, Brettell, Summerside, & McHanwell, 2009;Pereira et al, 2007). In fact, participants in one of the research project definitively outperformed those in the traditional curriculum (Pereira et al, 2007).…”
Section: ) Quantitative Commentsmentioning
confidence: 85%
“…One initiative is the use of videos to trigger active learning, leaving more time for interactions, questions and answers (Q&A), and for reflections. A quick literature review shows that the use of multimedia (videos) to achieve such aims has been attempted in other parts of the world, with fairly convincing outcomes (Catling, Williams, & Baker, 2014;Soh, Reed, Poulos, & Brennan, 2013). These include drug prescriptions, detecting radiological lesions, and in general pathology education (Thakore & McMahon, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…All final year medical students in the UK are now expected to successfully complete the Prescribing Skills Assessment in order to progress into the Foundation Programme 30. This assessment measures basic level competence upon entry into the workplace, but there are no further assessments thereafter.…”
Section: Discussionmentioning
confidence: 99%
“…Other medical schools have implemented prescribing e-tutorials for their students. Catling et al showed that students who completed these modules had a significantly increased confidence across all prescribing skills 4 ; national, widespread implementation of this may be effective. Prescribing tutorials aimed at reflecting on and tackling common errors could also be given to foundation year doctors to increase the knowledge and expertise as prescription errors are costly and detrimental to patient care.…”
mentioning
confidence: 99%